The Encyclopedia of DNA elements (ENCODE): data portal update. Issue Volume 46:Issue D1(2018) (6th November 2017) - Davis, Carrie A; Hitz, Benjamin C; Sloan, Cricket A; Chan, Esther T; Davidson, Jean M; Gabdank, Idan; Hilton, Jason A; Jain, Kriti; Baymuradov, Ulugbek K; Narayanan, Aditi K; Onate, Kathrina C; Graham, Keenan; et al.
Abstract: The Enc yclopedia o f D NA E lements (ENCODE) Data Coordinating Center has developed the ENCODE Portal database and website as the source for the data and metadata generated by the ENCODE Consortium. Two principles have motivated the design. First, experimental protocols, analytical procedures and the data themselves should be made publicly accessible through a coherent, web-based search and download interface. Second, the same interface should serve carefully curated metadata that record the provenance of the data and justify its interpretation in biological terms. Since its initial release in 2013 and in response to recommendations from consortium members and the wider community of scientists who use the Portal to access ENCODE data, the Portal has been regularly updated to better reflect these design principles. Here we report on these updates, including results from new experiments, uniformly-processed data from other projects, new visualization tools and more comprehensive metadata to describe experiments and analyses. Additionally, the Portal is now home to meta(data) from related projects including Genomics of Gene Regulation, Roadmap Epigenome Project, Model organism ENCODE (modENCODE) and modERN. The Portal now makes available over 13000 datasets and their accompanying metadata and can be accessed at: https://www.encodeproject.org/ .